Behaviour of radionuclides during microbially-induced mining of nickel at Talvivaara, Eastern Finland. (January 2016) - Tuovinen, Hanna; Pohjolainen, Esa; Lempinen, Janne; Vesterbacka, Daniela; Read, David; Solatie, Dina; Lehto, Jukka
Abstract: The Talvivaara mine in Eastern Finland utilizes microbe-induced heap leaching to recover nickel and other valuable metals (Zn, Cu, Co) from a black schist ore. In addition to the target metals, the ore contains uranium at a concentration of 17 mg/kg, incorporated as uraninite (UO2 ). Uranium oxidizes from the U(IV) to U(VI) state during leaching and dissolves as the uranyl ion ( U O 2 2 + ) in the acidic pregnant leach solution. Mobilisation of uranium has caused sufficient concern that plans have been developed for uranium recovery. The aim of this study is to generate new data leading to a better understanding of the fate of its radiotoxic daughter nuclides, primarily 226 Ra, 210 Pb and 210 Po, in the mining process. It is shown that uranium daughters mostly remain in the heaps during the leaching process and are associated with secondary minerals, including jarosite, goethite and gypsum. Thorium and progeny ( 232 Th plus 228 Th, 228 Ra) are also mainly retained. High sulphate concentrations in the acidic solutions limit the solubility of radium by incorporation in the crystal lattices of precipitated secondary sulphates. Electron probe microanalysis shows that goethite in the heaps is uraniferous, resulting from the adsorption of U(VI). After recovery of target metals, the pregnant leach solution is neutralized to further remove metal contaminants and the resulting slurries stored in a bunded tailings pond. The activity concentrations of thorium, radium, lead and polonium isotopes are generally low in the pond owing to prior retention by secondary minerals in the heaps. However, 238 U activity concentrations range up to 3375 Bq/kg, which exceeds the permitted value (1000 Bq/kg) for natural radionuclides of the 238 U series. Highlights: Uranium daughters mostly remain in the heaps during the leaching process. Uranium daughters are associated with secondary minerals. Thorium and progeny ( 232 Th plus 228 Th, 228 Ra) are mainly retained in the heaps. Uranium dissolves as the uranyl ion in the acidic pregnant leach solution. 238 U activity concentrations range up to 3375 Bq/kg in the gypsum pond.